The possibility using of turkey and chicken meats on the traditional pastrami production - Yusuf Doğruer (Eurasian Journal of Veterinary Sciences)
In this resarch it was aimed to determine the chemical and microbiological qualities of pastrami produced lom turkey and chicken meat by traditional methods and to compare these properties with cattle meat pastrami. According to the chemical analysis results significant differences were found in protein, (at. ash and salt contets during all of Ihe period in the pastramies produced from turkey, chicken and cattle meat and also there were significant differences in pH values and moisture content in all periods except alter coating with çemen. The result of microbiological examinations showed that there were significantly differences on total mesophil aerob and Staphylococcus-Micrococcus number in all periods, a significantly difference was determined in the mold and yeast number in all periods excepl after salting and all the periods after coating with çemen a significant difference on Lactobacillus number was seen and also a difference was seen on Enterobactericeae number before salting. No growth was seen on coliform group and Salmonella species in pastrami samples. As a result, it was concluded pastrami should be produced from turkey and chicken meat having similar properties with cattle meat pastrami. While the pastrami produced from turkey and chicken meat was acceptable microbiologically, problems were determined on moisture and salt contetnt according to chemical analysis findings. New technological methods should be used to avoid the problems occured at salting and drying process.